Students' attitude toward narcotic substances: the inhibitive role of legal and family forbiddances, inaccessibly to narcotics and trust to self - Ali Mohammad Rezaei; Mohammad Senobari (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The researches showed that the modification of peoples' attitude toward narcotic substances from positive to negative could be effective on inhibition of tendency and suffering of narcotics. The aim of present research was the study of students' attitudes toward narcotics and determination of the role of legal and family forbiddances, inaccessibly to narcotics and trust to self. Method: The research method was sectional survey study. In order to access to the aims the interest toward narcotics scale was administered among 400 students of Dezfol city that selected by clustering random sampling. Findings: factor analysis showed one factor in the scale. Reliability for total, boys, and girls students were 0.77, 0.81, and 0.70 respectively. The results of prevalence rate indicated that 18.3% of students sometimes thinking about narcotics, 12.5% of students interested to use narcotics even onetime, 11.8% of students considered the use of narcotics dreamy, 4.5% of students believed that the use of narcotics even onetime is worth the trouble, and 1.5% of students believed that the use of narcotics is appropriate for entertainment and funny. 10.5% of students indicated that they interested to use cigarettes. Also, the results showed if there was not legal and family forbiddances 9.3%, and 6.5% of students respectively used narcotics probably. Conclusion: In prediction of narcotics use legal and family forbiddances, inaccessibly of narcotics are important.